2002
DOI: 10.1093/nar/gkf506
|View full text |Cite
|
Sign up to set email alerts
|

Distinct domains in the CArG-box binding factor A destabilize tetraplex forms of the fragile X expanded sequence d(CGG)n

Abstract: Formation of hairpin or tetraplex structures of the FMR1 gene d(CGG)n sequence triggers its expansion, setting off fragile X syndrome. In searching for proteins that destabilize d(CGG)n secondary structures we purified from rat liver quadruplex telomeric DNA binding protein 42 (qTBP42) that disrupts G'2 bimolecular tetraplex d(CGG)n while paradoxically stabilizing the G'2 structure of the telomeric sequence d(TTAGGG)n. Based on peptide sequence homology of qTBP42 and mouse CArG-box binding factor A (CBF-A), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…Porcine CBF-A has two RNA recognition sites in the center of the molecule similar to rat CBF-A [20] (Fig. 1).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Porcine CBF-A has two RNA recognition sites in the center of the molecule similar to rat CBF-A [20] (Fig. 1).…”
Section: Discussionmentioning
confidence: 96%
“…The amplified DNA was directly sequenced, and its identity was confirmed with that of cDNA (data not shown). On the other hand, the ATP/GTP binding motif in the carboxyl region (residue numbers 282-290: GSTNYGKSQ) [22,23] is important for disruption of the tetraplex helix structure of G'2 d(CGG)n disruption [20,21]. This motif is present just behind a tract of glycine residues, which is different than in the human, rat and mouse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of fragile X syndrome is estimated at 1/4000--1/6000 in males and half that for females (Wiesner et al, 2004). This disease is linked to the mutation of the FMR1 gene located on the X chromosome, characterized by expansion (CGG amplification) at the FRAXA site (Xq27.3) in the non--coding region of the first exon (Weisman--Shomer et al, 2002). These authors also showed that two factors were indispensable for the stabilization of the CGG tetraplex: magnesium and ATP.…”
Section: Neurological Function Of Magnesiummentioning
confidence: 99%